2013
DOI: 10.1002/humu.22254
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Effect of GermlineTP53Missense Mutations in Li-Fraumeni Patients

Abstract: In contrast to other tumor suppressor genes, the majority of TP53 alterations are missense mutations. We have previously reported that in the Li-Fraumeni syndrome (LFS), germline TP53 missense mutations are associated with an earlier age of tumor onset. In a larger series, we observed that mean age of tumor onset in patients harboring dominant negative missense mutations and clearly null mutations was 22.6 and 37.5 years, respectively. To assess the impact of heterozygous germline TP53 mutations in the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 40 publications
2
44
1
Order By: Relevance
“…The identified TP53 (p.R248Q) mutation is a previously described gain-of-function mutation which is associated with early-onset development of many tumor types [3032]. The somatic APC (p.R790*) mutation has also been previously reported in the Catalogue Of Somatic Mutations In Cancer (COSMIC) database [33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…The identified TP53 (p.R248Q) mutation is a previously described gain-of-function mutation which is associated with early-onset development of many tumor types [3032]. The somatic APC (p.R790*) mutation has also been previously reported in the Catalogue Of Somatic Mutations In Cancer (COSMIC) database [33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Although a recent study evaluating the prevalence of germline mutations in children with cancer identified TP53 mutations in 4 of 46 patients with Ewing sarcoma, 26 there traditionally has been consensus that these mutations are not associated with Ewing sarcoma (F 1 sarcoma) susceptibility. 28 Two additional cases of Ewing sarcoma included in the International Agency for Research on Cancer database could not be confirmed by review of the reference publication. 28 Two additional cases of Ewing sarcoma included in the International Agency for Research on Cancer database could not be confirmed by review of the reference publication.…”
Section: Discussionmentioning
confidence: 99%
“…After superposition of the RT-QMPSF profiles generated from exposed and unexposed cells, by adjusting the CG peak heights, the expression fold-change is determined for each TG and the average of fold-changes yields an arbitrary genotoxicity score. One of the key aspects of the p53 genotoxicity assay is that the specificity of induction can easily be demonstrated by performing the same experiment in control lymphocytes derived from LFS patients, harboring heterozygous dominant-negative TP53 mutations that compromise the response to DNA damage [9].…”
Section: Description Of the P53 Genotoxicity Assaymentioning
confidence: 99%
“…Comparative gene expression profiling of wild-type and mutant (p.R248W; NP 000537.3) TP53 EBV-immortalized lymphocytes treated or not with doxorubicin, ethidium bromide, 5-FU, cisplatin or mitotic spindle poison (paclitaxel or vindesine) for 16 h was performed using Whole Human Genome Oligo 4 × 44 K Microarray (G4845A, Agilent), according to the Agilent Two-Color Gene Expression workflow as previously described [9]. Briefly, starting from 100 ng of total RNA, cRNA was synthesized and labelled using the low input Quick Amp Labeling Kit (Agilent), with Cy3 (for unexposed cells) and Cy5 (for exposed cells).…”
Section: Microarray Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation